(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
This paper presents a detailed analysis of Multicarrier Code Division Multiple Access (MC-CDMA) system over Additive White Gaussian Noise (AWGN) and Rayleigh Fading Channel with analysisof the effects of different number of sub-carriers and multiuser scenarios and at the end a comparison with standard technique is also performed. The complete analysis is performed by simulating the mathematical model of the MC-CDMA system with various combinations of sub-carriers, number of users, SNR, path gains and path delays etc. the simulation results shows that the MC-CDMA is an effective way to overcome the multipath fading losses and spectrum utilization with relatively simple system architecture.